Innovative Digital Mapping of Soil Organic Matter Content in Oil Palm Using Image Analysis - Ida Ratna Nila; Rahmawati Rahmawati; Muhammad Ari Fahril; Sabrian Tri Anda; Rachmad Almi Putra; Fajriani Fajriani; Afrahun Naziah (Jurnal Ilmu Pertanian Indonesia, 2026)
The goal of this study is to use image processing technology to map the organic matter content of soil in oil palm plantations. The data set comprises photos of oil palms and bare land, as well as field measurements of pH, humidity, temperature, total dissolved solids, and electrical conductivity. Correlation analysis revealed a strong link between picture spectral components (particularly in the blue channel, r = 0.3640) and soil organic matter content. The distribution of organic matter content ranges from 4.5 to 5.5%, with an average of around 5%. The image processing-based predictive model successfully mapped the spatial variation of organic matter content with high accuracy. The mapping results demonstrate spatial variability, which can be exploited to support precision agriculture in oil palm areas. Keywords: soil organic matter, image processing, oil palm, mapping, precision agriculture